Factors Affecting Unhappiness at School among Japanese Adolescents: An Epidemiological Study - Morioka, Hisayoshi (PLoS One, 2014)
BACKGROUND: Unhappiness at school is one of the main reasons for truancy among adolescents. In order to assess this problem more thoroughly in the context of Japanese adolescents, the present study examined the associations between feelings of unhappiness at school and lifestyle habits, school life realities, and mental health status. METHOD: This study was designed as a cross-sectional survey. A self-administered questionnaire was provided to students enrolled in randomly selected junior and senior high schools throughout Japan. We calculated the percentages of both junior and senior high school students who felt unhappy at school based on factors related to school life, lifestyle habits, and mental health status. Multiple logistic regression analyses were performed in order to examine the associations between those factors and students' feelings of unhappiness at school. RESULTS: A total of 98,867 valid responses were analysed, 7.9% (Boys: 8.4%, Girls: 7.4%) of which came from students who responded that they felt unhappy at school. For both junior and senior high school students, the percentages of those who felt unhappy at school were significantly higher among those who had not yet decided on their future life course, who did not participate in extracurricular activities, did not eat breakfast every day, went to bed late, had used tobacco or alcohol in the previous 30 days, and had poor mental health compared with others. The results of multiple logistic regression analyses indicated that the adjusted odds ratios for feeling unhappy at school with regard to the above-mentioned factors were significantly high for both junior and senior high school students. CONCLUSIONS: The present results suggest that school employees and administrators must provide health guidance to students, considering that irregular lifestyle habits, lower school engagement, smoking, drinking alcohol, and poor mental health status are all associated with maladaptation to school among adolescents.